Effect of Jian-Pi-Zhi-Dong Decoction on striatal glutamate and γ-aminobutyric acid levels detected using microdialysis in a rat model of Tourette syndrome - Zhang W; Wei L; Yu W; Cui X; Liu X; Wang Q; Wang S (Neuropsychiatric Disease and Treatment, 2016)
Wen Zhang,1,* Li Wei,2,* Wenjing Yu,1 Xia Cui,1 Xiaofang Liu,2 Qian Wang,1 Sumei Wang2 1Department of Pediatrics, The Third Affiliated Hospital, 2Department of Pediatrics, Dongfang Hospital, Beijing University of Chinese Medicine, Beijing, People’s Republic of China *These authors contributed equally to this work Background: Jian-Pi-Zhi-Dong Decoction (JPZDD) is a dedicated treatment of Tourette syndrome (TS). The balance of neurotransmitters in the cortico-striato-pallido-thalamo-cortical network is crucial to the occurrence of TS and related to its severity. This study evaluated the effect of JPZDD on glutamate (Glu) and γ-aminobutyric acid (GABA) and their receptors in a TS rat model.Materials and methods: Rats were divided into four groups (n=12 each). TS was induced in three of the groups by injecting them with 3,3'-iminodipropionitrile for 7 consecutive days. Two model groups were treated with tiapride (Tia) or JPZDD, while the control and the remaining model group were gavaged with saline. Behavior was assessed by stereotypic score and autonomic activity. Striatal Glu and GABA contents were detected using microdialysis. Expressions of N-methyl-D-aspartate receptor 1 and GABAA receptor (GABAAR) were observed using Western blot and real-time polymerase chain reaction.Results: Tia and JPZDD groups had decreased stereotypy compared with model rats; however, the JPZDD group showed a larger decrease in stereotypy than the Tia group at a 4-week time point. In a spontaneous activity test, the total distance of the JPZDD and Tia groups was significantly decreased compared with the model group. The Glu levels of the model group were higher than the control group and decreased with Tia or JPZDD treatment. The GABA level was higher in the model group than the control group. Expressions of GABAAR protein in the model group were higher than in the control group. Treatment with Tia or JPZDD reduced the expression of GABAAR protein. In the case of the mRNA expression, only Tia reduced the expression of N-methyl-D-aspartate receptor 1, compared with the model group.Conclusion: JPZDD could alleviate impairments in behavior and dysfunctional signaling by downregulating GABAAR in the striatum. We suggest that this acts to maintain the balance of Glu and GABA. Keywords: amino acid neurotransmitter, cortico-striatal-thalamic-cortical, stereotypy, autonomic activity, GABAAR, NMDAR1